Proteomic identification of extracellular proteins regulated by the Gna1 Gα subunit in Stagonospora nodorum - Tan, Kar-Chun; Heazlewood, J.; Millar, A.; Oliver, Richard; Solomon, P. (Elsivier, 2009)
The fungus Stagonospora nodorum is the causal agent of stagonospora nodorum blotch (syn.leaf and glume blotch) disease of wheat. The Gna1-encoded Ga protein is an important signaltransduction component in the fungus, which is required for full pathogenicity, sporulationand extracellular depolymerase production. In this study, we sought to gaina better understanding of defects associated with the gna1 mutant by using twodimensionalgel electrophoresis to analyse the extracellular proteome for differences tothe wildtype. Mass spectrometry analysis of altered abundant protein spots and peptidematching to the Stagonospora nodorum genome database have led to the identification ofgenes implicated in cell wall degradation, proteolysis, RNA hydrolysis and aromatic compoundmetabolism. In addition, quantitative RT-PCR has demonstrated that some of theencoding genes showed differential expression throughout host infection. Implicationsof these proteins and their corresponding genes in fungal virulence are discussed.The fungus Stagonospora nodorum is the causal agent of stagonospora nodorum blotch (syn. leaf and glume blotch) disease of wheat. The Gna1-encoded Gα protein is an important signal transduction component in the fungus, which is required for full pathogenicity, sporulation and extracellular depolymerase production. In this study, we sought to gain a better understanding of defects associated with the gna1 mutant by using two-dimensional gel electrophoresis to analyse the extracellular proteome for differences to the wildtype. Mass spectrometry analysis of altered abundant protein spots and peptide matching to the Stagonospora nodorum genome database have led to the identification of genes implicated in cell wall degradation, proteolysis, RNA hydrolysis and aromatic compound metabolism. In addition, quantitative RT-PCR has demonstrated that some of the encoding genes showed differential expression throughout host infection. Implications of these proteins and their corresponding genes in fungal virulence are discussed.